2018
DOI: 10.1186/s13058-018-1015-x
|View full text |Cite
|
Sign up to set email alerts
|

A phase Ib study of pictilisib (GDC-0941) in combination with paclitaxel, with and without bevacizumab or trastuzumab, and with letrozole in advanced breast cancer

Abstract: BackgroundThis phase Ib study (NCT00960960) evaluated pictilisib (GDC-0941; pan-phosphatidylinositol 3-kinase inhibitor) plus paclitaxel, with and without bevacizumab or trastuzumab, or in combination with letrozole, in patients with locally recurrent or metastatic breast cancer.MethodsThis was a three-part multischedule study. Patients in parts 1 and 2, which comprised 3 + 3 dose escalation and cohort expansion stages, received pictilisib (60–330 mg) plus paclitaxel (90 mg/m2) with and without bevacizumab (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…Likewise, in HER2-positive BC patients, presence of a PIK3CA-mut is associated with worse response rates to neoadjuvant treatment [62]. Phase I/II studies demonstrated the overall feasibility of combining anti-HER2 treatments with PI3Ki (Table 2) [46,[50][51][52][53][54][55][56][57][58][59]63]. A phase II study including HER2-positive, trastuzumab-resistant metastatic BC patients treated with buparlisib and trastuzumab showed an overall response rate of 10%, but grade !…”
Section: With Anti-her2 Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in HER2-positive BC patients, presence of a PIK3CA-mut is associated with worse response rates to neoadjuvant treatment [62]. Phase I/II studies demonstrated the overall feasibility of combining anti-HER2 treatments with PI3Ki (Table 2) [46,[50][51][52][53][54][55][56][57][58][59]63]. A phase II study including HER2-positive, trastuzumab-resistant metastatic BC patients treated with buparlisib and trastuzumab showed an overall response rate of 10%, but grade !…”
Section: With Anti-her2 Agentsmentioning
confidence: 99%
“…In most clinical studies evaluating PIK3CA-mut as a predictor of chemotherapy response in BC, inferior response rates were observed in patients with PIK3CA-mut tumours when compared with patients with PIK3CA-wild-type tumours [62,65]. Therefore, the combination of PI3Ki and chemotherapy is being investigated as an attempt to overcome treatment resistance, but no promising results have been observed so far (Table 2) [9,11,21,49,59]. Ongoing trials are evaluating the association of PI3Ki with chemotherapy in HER2-negative BC (Table 3).…”
Section: With Chemotherapymentioning
confidence: 99%
“…Moreover, PI3K and PI3K/mTOR inhibitors tested in a clinical setting (e.g. pictilisib 21 and apitolisib 22 ) have suffered from toxic effects 23,24 . Thus, identification of compounds that increase the therapeutic index for PI3K inhibitors could enable new uses for PI3K inhibition in oncology.…”
Section: Background and Summarymentioning
confidence: 99%
“…PI3K mutational status is often not predictive of response to PI3K-targeted drugs. For example, only a subset of patients with mutant PI3K responded to pictilisib in clinical trials (Krop et al, 2016;Schmid et al, 2016;Schöffski et al, 2018). The edge flux and the median marker expression suggest important roles of p-MKK4 and p-STAT3 in defining pictilisib sensitivity; both have potential as markers for improving patient stratification.…”
Section: Discussionmentioning
confidence: 99%